Oxford children's encyclopedia (Cannibalism-Egypt 2) - Oxford university press (Oxford : Oxford University Press, c2004. oxford., 1991)
A useful reference work for children of 8 years and over. The features include: the 'war against terrorism', including the Afghan and Iraq wars; the genetic revolution (cloning, GM foods, the Human Genome Project); technological developments, such as digital photography and DVDs; and the introduction of the euro and the expansion of the EU.
Keywords: Cannibalism, Egypt, Children's encyclopedias